Immigrant patients in brief meetings with anaesthetist nurses – experiences from perioperative meetings in the orthopaedic setting - Ferid Krupić; Kemal Grbić; Svemir Čustović; Eric Hamrin Senorski; Kristian Samuelsson (Medicinski glasnik, 2018)
Aim: To explore the experience of anaesthetist nurses in brief meetings with immigrant patients in the perioperative setting. Methods: The study was conducted through open individualised interviews using open-ended questions. Eighteen anaesthetist nurses (six men and twelve women) participated in the interviews. Their age varied between 35 and 65 and they had worked as anaesthetist nurses for a period between six and twenty eight years. The text was analysed using qualitative content analysis. Results: Meetings with immigrant patients made nurses with less experience to prepare more, to study behaviour of these patients and to ask their older colleagues for advice. More experienced nurses acted on the basis of their previous experience and treated the patients in the same way as before. They also emphasised the great responsibility and wider scope of assistance needed by these patients than those born in Sweden. The majority of nurses begin the meetings with these patients by requesting an interpreter, while some nurses begin the meeting directly with the patient and, if they see it is not going well, they request an interpreter. Conclusion: Nurses need better guidelines and education in how to deal with the legislation relating to immigrant patients in order to handle the situation more effectively. Training in cross-cultural care should be improved to help nurses deal with stress through cooperation with the Migration Board and others. In order to provide for good communication and patient safety professional interpreters should be used.
Keywords: anaesthetist nurses; brief meeting; experiences; immigrant patients; qualitative research